The Phonetic Description of Eshtehrdi Dialect - محمّد پارسانسب (مطالعات زبانی و بلاغی, 2011)
Identification, collecting and studying on the local dialects, cause not only consolidation of cultural relation between today and yesterday, but also prevent destruction of dialects and provide a condition for improving and developing of national language and culture. Eshtehardi Tatty dialect, the dialect of the south-west Iran, with all that antiquity, is still alive and regarding its geographic region, had been remained intact until a few decades ago. But now for various reasons is eliminated against the power of national language. The presence of some elements of relation with the ancient language in this dialect, the maintenance of relation with the ancient languages of Iran and also the extent of lexical scope and diversity of grammatical structures are the main features of this dialect. In this article, according to a phonetic comparison between the common words of this dialect with Persian language, we have tried to present a clear picture of its phonetic features. Such a work has not been done so far and it can be very useful in understanding the nature of Tatty dialect and in discovering the relation and interaction of this dialect with the dialects in the same root. Our study shows that the phonetic distinctions of Tatty dialect with the Persian language appears in the first, middle and final part of words, and follows four phonological transformation, deletion, addition and metathesis.